Slovene-Croatian Treebank Transfer Using Bilingual Lexicon Improves Croatian Dependency Parsing - Agić, Željko (Array, 2012)
A method is presented for transferring dependency treebanks between similar languages by using a bilingual lexicon, aiming to improve dependency parsing accuracy on the target language. It is illustrated by transferring the Slovene Dependency Treebank to Croatian by using a GIZA++ bilingual lexicon constructed from the Croatian-Slovene 1984 parallel corpus from the Multext East project. The transferred treebank is merged with the Croatian Dependency Treebank and the merged treebank is used to train and test two graph-based dependency parsers. MSTParser and CroDep accuracy on parsing the 1984 ﬁctional text shows a statistically signiﬁcant increase and a similar decrease on parsing the Croatian Dependency Treebank newspaper text.